1998
DOI: 10.1002/(sici)1097-4628(19980214)67:7<1205::aid-app6>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of polyaniline-polystyrene blends above the percolation threshold

Abstract: ABSTRACT:Blends of conductive polymers with classical ones can exhibit good mechanical properties and good electrical conductivity and deserve great attention for application in electronic industrial technology. Conductive polyaniline solutions have been chemically prepared using bis(2-ethyl hexyl)hydrogen phosphate (DiOHP) as the dopant chemical species. The codissolution method leads to conductive polyanilinepolystyrene (PANI-PSt) composites with good mechanical properties. The dependence of electrical condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 3 publications
3
30
1
2
Order By: Relevance
“…Aqueous PEDOT:PSS suspensions are commercially available in various grades, and have found widespread use in photovoltaic and light-emittingdiode applications. [36] Heeger and coworkers blended a conductive polymer, PANI, with insulating PS or poly(methylmethacrylate) [54,55] to give PANI nanowires percolating the insulating matrix, even at low loading (< 1 vol % PANI). Solvents/additives with high boiling points have been used to selectively remove excess PSS and crystallize PEDOT, with work by Pipe and co-workers demonstrating the highest ZT (0.42) for a p-type organic system by adding 5 vol % DMSO to the PEDOT:PSS solution, thermally annealing the film, and immersing it in ethylene glycol (EG).…”
Section: Polymer Blended With Polymers and Small Moleculesmentioning
confidence: 99%
“…Aqueous PEDOT:PSS suspensions are commercially available in various grades, and have found widespread use in photovoltaic and light-emittingdiode applications. [36] Heeger and coworkers blended a conductive polymer, PANI, with insulating PS or poly(methylmethacrylate) [54,55] to give PANI nanowires percolating the insulating matrix, even at low loading (< 1 vol % PANI). Solvents/additives with high boiling points have been used to selectively remove excess PSS and crystallize PEDOT, with work by Pipe and co-workers demonstrating the highest ZT (0.42) for a p-type organic system by adding 5 vol % DMSO to the PEDOT:PSS solution, thermally annealing the film, and immersing it in ethylene glycol (EG).…”
Section: Polymer Blended With Polymers and Small Moleculesmentioning
confidence: 99%
“…It has been reported that the composite system by blending PANI with a commodity polymer improves its mechanical properties [8][9][10][11]. It has also been proposed that the incorporation of side groups into the main chain [12], grafting of the conducting PANI chain to a non-conductive polymer [13] and electrochemical polymerization of aniline in a polymer matrix [14] improve their processibility and thus broaden their applicability. A large amount of PANI-inorganic composites like PANI/V 2 O 5 [15], PANI/TiO 2 [16][17][18], PANI/CdS [19], PANI/graphite oxide [20] and PANI/clay [21,22], etc have been synthesized and studied to enhance the overall Silver sulphate, ammonium persulphate, HCl and H 2 SO 4 were used as received.…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts were made to combine the mechanical properties of insulating polymers with CP, involving composites and blends, such as PANI mixed with epoxy resin, to produce materials with anti-corrosion properties [12] ; blends of PANI and lignin to study modification in the thermal properties of CP [13] and PANI with polystyrene (PS) to investigate electrical and thermal properties [14] . The mixing of CP with insulating polymers presents the advantage of producing materials with good mechanical properties associated with attractive electrical properties [15] . In this work, the POMA was doped with camphor sulfonic acid (CSA) and POMA/poly(methyl methacrylate) (PMMA) blends were prepared with two levels of doping and its optical, morphological and electrical properties were analyzed.…”
Section: Introductionmentioning
confidence: 99%